2011
DOI: 10.1093/molehr/gar071
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling in mouse oocyte maturation: the roles of STIM1, ORAI1 and SOCE

Abstract: Calcium handling is critical for the oocyte function, since the first steps of fertilization are dependent on the appropriate Ca(2+) mobilization to originate transient spikes of the cytosolic Ca(2+) concentration. It is well known that the Ca(2+) influx from the extracellular milieu is required to maintain this signaling in mammalian oocytes. However, the regulation of the Ca(2+) channels involved in this process is still unknown in oocytes. STIM1, a key regulator of store-operated Ca(2+) entry (SOCE), reloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
1
32
2
Order By: Relevance
“…The distribution of STIM1 and Orai1 we observe is distinct from that previously reported in mouse oocytes (Gómez-Fernández et al, 2009;Gómez-Fernández et al, 2012) where STIM1 was described to localize to distinct vesicular-like ER structures before store depletion and to large ER areas after store depletion. Orai1 distribution was described as patchy membrane localized in MII eggs.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The distribution of STIM1 and Orai1 we observe is distinct from that previously reported in mouse oocytes (Gómez-Fernández et al, 2009;Gómez-Fernández et al, 2012) where STIM1 was described to localize to distinct vesicular-like ER structures before store depletion and to large ER areas after store depletion. Orai1 distribution was described as patchy membrane localized in MII eggs.…”
Section: Discussioncontrasting
confidence: 93%
“…Surprisingly however in both mouse and pig oocytes previous reports detected little or no SOCE in GV oocytes (Gómez-Fernández et al, 2012;Wang et al, 2012). In contrast we detect a robust SOCE in GV oocytes in the mouse that is significantly larger than that measured in MII cells.…”
Section: Discussioncontrasting
confidence: 92%
“…relation was demonstrated between Ca 2+ oscillation and STIM1 expression and activity, other studies showed a link between cell proliferation/apoptosis, PLC, NF-κB, STIM1, Orai1 and Ca 2+ oscillations [43,[88][89][90][91][92].…”
Section: Deletion Of Stim Protein Expression In T Reg Cells Influencementioning
confidence: 82%
“…The studies imply that primary function of a large Ca 2+ oscillatory signals might be ensure sufficient store depletion by robust activation of CRAC channels through STIM1, activating downstream signal transduction [43,[88][89][90][91][92]. Additionally, two different transcription factors, c-fos and NFAT were shown to promote local Ca 2+ elevations near open CRAC channels and activate gene expression [42,93].…”
Section: Deletion Of Stim Protein Expression In T Reg Cells Influencementioning
confidence: 96%
“…Based on these observations, SOCE, which relies upon detection of low ER Ca 2+ by STIM1 and STIM2 proteins, which promote Ca 2+ influx through ORAI channels (reviewed in Bird et al, 2008;Putney, 2007), might be considered a prime candidate for mediating the Ca 2+ influx needed to sustain Ca 2+ oscillations in mammalian eggs. Although SOCE components are present in mouse oocytes and eggs (Cheon et al, 2013;, and previous reports have suggested that SOCE might be active during mammalian oocyte maturation and fertilization (Cheon et al, 2013;Gomez-Fernandez et al, 2012Lee et al, 2012;Wang et al, 2012Wang et al, , 2015, evidence against a requisite role for SOCE is also mounting. We have previously shown that chemical inhibition of SOCE following fertilization does not impair Ca 2+ oscillations or egg activation events .…”
Section: Camentioning
confidence: 99%